Sustainable materials and technologies : for design and construction of pavements - Remišová, Eva; Decký, Martin; Papán, Daniel (Pearson, 2025)
Adaptable, automated and resilient to climate change, the new generation of roads shozld also be able to meet future user/community demands for reliable, accessible, sustainable, safe, low-cost and environmentally friendy road transport. In assessing the sustainability of road construction, economic, social and environmental criteria are considered in their interrelatedness. The present scientific monograph brings new knowledge in the field of sustainable materials and technologies used in the construction of road pavement structures as: - composite concrete with polyester and vinylester resins; - composite foam concrete; - warm-mix and cold-mix asphalts; - recycled asphalt. The autors aimed to provide the latest knowledge to researchers and professionals working in the fields of road pavement design and construction, testing, and materials engineering, because meeting the demanding requirements of a road pavement depends on responsible structural design and the selection of appropriate materials and technologies